Experimental investigation of a novel mechanically fluidized bed reactor for thermochemical energy storage with calcium hydroxide/calcium oxide. (1st June 2022) - Risthaus, Kai; Linder, Marc; Schmidt, Matthias
Graphical abstract: Highlights: A novel reactor concept based on a mechanically induced fluidization was implemented. Thermal charge and discharge of CaO/Ca(OH)2 was successfully demonstrated. Performance in terms of the effective heat transfer coefficient was determined. Heating up of CaO and dehydration of Ca(OH)2 yield 156 and 243 W/m 2 /K, respectively. Fluidization mode yields about 8 times higher power density compared to fixed bed. Abstract: The reaction system based on the reversible hydration of CaO is promising for thermochemical energy storage since the material is a non-toxic, cheap industrial mass product with a comparatively high reaction enthalpy. However, the fine cohesive powder has a low thermal conductivity as well as a limited flowability and is not easily fluidized. Therefore, a reactor realization is challenging especially for higher capacities when the reactor cannot be the storage unit simultaneously. We developed a novel reactor concept based on a plow share mixer, demonstrated its feasibility and investigated its heat and mass transfer performance. In this concept, a rotating mixing device mechanically fluidize the bed in the reactor without the necessity of a gas flow, which might be especially advantageous for smaller power reactors. Both reaction directions have been successfully demonstrated. However, in the present configuration, the formation of a CaO/Ca(OH)2 layer on the heat transferring surface of the reactor reduces the heat transfer coefficient. Another layer formed on the filter, separating the reactor from the condenser, limited the gas transport and thereby dominated the conversion rate of the dehydration. Despite these limitations the mechanical fluidization yields significantly improved heat transfer compared to fixed bed reactors. One main parameter characterizing the performance of the reactor is the effective heat transfer coefficient from the electrically heated wall to the mechanically fluidized bed which was determined to be 156 ± 16 W/m 2 /K and 243 ± 52 W/m 2 /K for the heating up of CaO and the dehydration of Ca(OH)2, respectively.